2022
DOI: 10.3390/ani12030354
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hard Ticks (Ixodidae) Infestation with Milk Production and Udder Health of Extensively Reared Dairy Goats

Abstract: Extensively reared ruminants are seasonally exposed to ticks. Tick-related production losses and health issues have been well documented in cows and sheep but not in goats where relevant literature is scarce. The objective here was to investigate the association of hard tick infestation with milk production and udder health of dairy goats reared extensively. A cross-sectional study was carried out during May and June, in two dairy goat farms. The farms were located in Central and Northern Greece and were repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…However, this would require the collection of accurate pedigree data. As previously indicated, in low-input pastoral farming systems, pedigree recording is hindered by poor infrastructure, uncontrolled natural mating, and absence of artificial insemination [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Moreover, farmers are not well informed of the benefits of genetic improvement and reluctant to invest time and resources in record keeping [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this would require the collection of accurate pedigree data. As previously indicated, in low-input pastoral farming systems, pedigree recording is hindered by poor infrastructure, uncontrolled natural mating, and absence of artificial insemination [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Moreover, farmers are not well informed of the benefits of genetic improvement and reluctant to invest time and resources in record keeping [20].…”
Section: Discussionmentioning
confidence: 99%
“…We also defined an overall endoparasite infection index, where at least one of these parasites was detected. Moreover, the presence of at least 10 ticks attached to the body of goats was considered as tick infestation [6,33]. A myiasis case was defined by the presence of at least two warbles beneath the skin on the back of the animal.…”
Section: Phenotypic Data Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the current findings, Gebremedhin et al [ 37 ] found a direct correlation between tick infestation and the prevalence rate of S. aureus in milk samples, as well as an inverse correlation between teat washing before milking and the isolation rate of S. aureus . Vouraki et al [ 38 ] also reviewed that there have been reports of S. aureus isolation from Rhipicephalus spp. tick.…”
Section: Discussionmentioning
confidence: 99%